2011
DOI: 10.1644/10-mamm-a-226.1
|View full text |Cite
|
Sign up to set email alerts
|

Incisor morphology reflects diet in caviomorph rodents

Abstract: Rodents are important components of most modern ecosystems. Understanding their roles in paleocommunities requires robust methods for inferring diet and other autecological characteristics. This pilot study tests whether a relationship between incisor morphology and diet exists among extant rodents that might be used to infer diets of extinct species. We focused on 11 genera of caviomorph rodents classified in 3 dietary categories: fruit-leaf, fruit-seed, and grass-leaf. For each genus 6 variables describing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 56 publications
(30 reference statements)
1
32
0
Order By: Relevance
“…Most living rodents are herbivorous or omnivorous while some species are carnivores, piscivores, and insectivores (Samuels 2009). Caviomorphs can be regarded as mainly herbivorous (Croft et al 2011), while some echimyids species are omnivorous or at least incorporate some animal material (Nowak 1991); insectivory has been proposed for some extant echimyids and fossil octodontoids (Vucetich and Verzi 1996;Lessa and Costa 2009). Broadly, herbivores can be split into generalized and specialist categories (Samuels 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most living rodents are herbivorous or omnivorous while some species are carnivores, piscivores, and insectivores (Samuels 2009). Caviomorphs can be regarded as mainly herbivorous (Croft et al 2011), while some echimyids species are omnivorous or at least incorporate some animal material (Nowak 1991); insectivory has been proposed for some extant echimyids and fossil octodontoids (Vucetich and Verzi 1996;Lessa and Costa 2009). Broadly, herbivores can be split into generalized and specialist categories (Samuels 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ingestion of intrinsic and exogenous abrasives by graminivorous species is related to an increase in tooth wear and the degree of hypsodonty (Williams and Kay 2001). Among caviomorphs, taxa that are known to feed on grass have hypsodont molars (see Williams and Kay 2001), whereas the diet of living taxa that present low-crowned teeth, as is the case of living echimyids, includes leaves and fruits and may incorporate insects (Nowak 1991;Croft et al 2011). Hence, the overall moderate development of the masticatory musculature displayed by Prospaniomys could suggest an omnivorous or generalized herbivorous diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, the dietary selectivity of both rodents (Escobar and González-Jiménez 1976, Quintana et al 1998, Quintana 2002, Guichón et al 2003a, Borges and Colares 2007, Galende et al 2013, the relative palatability of the plants available for foraging, and the strong relationship between energy content and fiber (Molano 1994, Colares et al 2010) explain a number of the similarities observed between the diets of the two rodents. Another characteristic to note is the similarity of the morphology of the oral apparatus, e.g., the incisor teeth of both rodents, which can directly shape the similarity between species in the use of food resources (Croft and Niemi 2011).…”
Section: Similar Results Have Been Obtained By Other Studiesmentioning
confidence: 99%
“…Upper incisors of Rhabdomys pumilio with the measurements adapted from Croft et al [28] marked. Abbreviations: BD, buccolingual diameter; DE, distal enamel extent; MD, mesiodistal diameter; OD, buccolingual occlusal diameter; RC, outer radius of curvature; OA, occlusal angle.…”
Section: Methodsmentioning
confidence: 99%